To inhibit growth and migration of glioma cells through down regulation glucose metabolism related to aquaporin (AQP)-1 - Liu, Xiangming; Chen, Jinglong; Zhang, Jinqian (Translational Cancer Research; Vol 7, No 6 (December 30, 2018): Translational Cancer Research, 2018)
Background: Glioma is one of highly aggressive and fastest growing human tumors. aquaporin (AQP)-1 is a critical factor in cell function, especially in glioma cells. However, its mechanism is unknown. Here, we explored growth and migration mechanism of glioma cells associated with glucose metabolism regulated by AQP-1. Methods: The growth and migration of glioma cells were analyzed after up or down regulation of AQP-1 expression. The expression of glucose metabolism-related proteins G6PC (glucose-6-phosphatase, catalytic subunit), GK (glycerol kinase), and GOT1 (glutamic-oxaloacetic transaminase 1) were examined. Glucose production of glioma cells was determined with colorimetric glucose oxidase method. Results: Our work indicated that AQP-1 facilitated growth and migration of glioma cells by regulating glucose metabolism, which was related to down-expression of gluconeogenesis gene G6PC, GK and GOT1. Interference on AQP-1 expression suppressed these processes of glioma cells. Conclusions: Therefore, our data demonstrated that down regulation of AQP-1 can induce the inhibition of glioma cell growth and migration through the pathway related to gluconeogenesis gene G6PC, GK and GOT1, which may promote the glucose metabolism. AQP-1 is the potential novel target for treatment of glioma.